Dynamics of water status during fruiting body development of Agaricus bisporus and its relationship to mushroom quality - Lingzhong Wan; Hui Sun; Ying Ni; Jun Tang; Junjie Yu; Juan Wu; Xiaoming Yan; Xiaonan Deng (Chemical and Biological Technologies in Agriculture)
Abstract Background The analysis of changes in subcellular water distribution during mushroom fruiting is essential for elucidating the movement of water molecules within subcellular compartments. However, prior research on mushrooms has predominantly concentrated on alterations in water status during drying and postharvest processes in the food processing sector. Knowledge regarding subcellular water compartments throughout mushroom growth and fruiting remains limited. In the present study, the dynamics of subcellular water status across various growth stages of Agaricus bisporus were investigated using LF-NMR relaxometry. Results Three components were resolved from transverse relaxation curves, assigned to cell wall, cytoplasmic and vacuolar water, in both whole mushroom and mushroom tissues (stalk and Pileus). As fruiting body developed, the proton degree of freedom of three water fractions determined by T2 measurement all increased. The T2 values of three water fractions in stalk were higher than those in pileus during the first three stages, whereas they became lower compared to those in pileus from somewhere between the two stages of 2–3 and 3–4. Apparently different patterns of change in three water contents were observed, indicating the variations in water distribution at subcellular level. Furthermore, relative humidities caused obvious changes in water status. In addition, highly significant correlations were observed between T2 and textural parameters, indicating that the dynamics of water status exert a substantial influence on the formation of mushroom quality. Conclusions A consistent increase in the transverse proton degree of freedom of three distinct water fractions, accompanied by markedly divergent patterns in the variations of the three water contents, was observed across different growth stages of fruiting bodies. Subsequently, highly significant correlations between T2 and textural parameters were established. This study would contribute to reveal macroscopic water transport within mushroom tissues and provide theoretical insights for optimizing high-quality mushroom cultivation. Graphical Abstract